2016
DOI: 10.1140/epjc/s10052-016-4245-z
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-matter bounce and inflation in the light of the CSL model

Abstract: The continuous spontaneous localization (CSL) model has been proposed as a possible solution to the quantum measurement problem by modifying the Schrödinger equation. In this work, we apply the CSL model to two cosmological models of the early Universe: the matter bounce scenario and slow roll inflation. In particular, we focus on the generation of the classical primordial inhomogeneities and anisotropies that arise from the dynamical evolution, provided by the CSL mechanism, of the quantum state associated to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 67 publications
(201 reference statements)
1
18
0
1
Order By: Relevance
“…We found that, by including collapses, the results are different from the standard case, but also that, under certain particular conditions, similar results can be obtained. 5 For instance, in [8,10,25] it was shown that very particular CSL types of models, based on approach (i), could be consistent with both the CMB observations and constraints coming from non-relativistic laboratory situations. 6 Therefore, in a certain sense, even omitting the serious problems mentioned in (i), the results in [11] should be interpreted as merely "casting a shadow" on another particular type of CSL model, which is different from the ones considered in [8,10,25].…”
Section: Gravitation and Quantum Field Theorymentioning
confidence: 90%
“…We found that, by including collapses, the results are different from the standard case, but also that, under certain particular conditions, similar results can be obtained. 5 For instance, in [8,10,25] it was shown that very particular CSL types of models, based on approach (i), could be consistent with both the CMB observations and constraints coming from non-relativistic laboratory situations. 6 Therefore, in a certain sense, even omitting the serious problems mentioned in (i), the results in [11] should be interpreted as merely "casting a shadow" on another particular type of CSL model, which is different from the ones considered in [8,10,25].…”
Section: Gravitation and Quantum Field Theorymentioning
confidence: 90%
“…With these modifications, theoretical predictions can be made, which then allow these theories to be tested and thus be able to say something about their viability to explain the precise observations, for example, of the CMB. Some predictions have proved very interesting since they have been able to explain certain observational constraints in a more natural and clear way than in the standard case (see for instance, [47][48][49][50][51][52][53][54][55][56][57]) 20 .…”
Section: Facing the Problem And Other Related Issuesmentioning
confidence: 99%
“…The implementation of the CSL model into the picture of slow-roll inflation has been analyzed in previous work [42,[46][47][48] (in Refs. [43][44][45] the CSL model is also considered during inflation but based on a different conceptual approach).…”
Section: The Csl Model During Inflationmentioning
confidence: 99%
“…(16). Equation (47), also serves to illustrate the effect of the collapse. As long as λ H 1 the uncertainty of the field δ 2 Qφ will start to decrease with respect to the uncertainty in the vacuum state as expected from a reduction of the wave function.…”
Section: Modification Of the Standard Picturementioning
confidence: 99%